Spatiotemporal Distribution of Case Fatality Rate of Coronavirus Disease 2019 (COVID-19) in Libya - Abdusalam Sharef Mahmoud; Hafsa A. Alemam; Ahlam Masaud Ellafi; Mouna A. Abdunnabi; Ahmed A. Zaghdani; Salah Edin El Meshri; Adam Elzghied (المجلة الأفروآسيوية للبحث العلمي, 2024)
Severe acute respiratory syndrome coronavirus 2 is the respiratory disease responsible for the COVID-19 pandemic; one of the worst pandemics reported throughout human history with a high Case fatality rate reported leading to high potential impacts and lockdown of the entire world’s activities. This study assessed and determined the Case fatality rate of COVID-19 and its associated risk factors among the Libyan population. A retrospective cohort study involving 1,000 random nasal swabs from Libya between July 2020 and January 2021 examined the presence of coronavirus antigens in samples from different regions and sexes using a real-time reverse transcriptase-polymerase chain-reaction assay at the Libyan Centre for Biotechnology, Tripoli, Libya. The overall case fatality rate was estimated to be (4.7%; 3.37%-5.99%) with a 95% confidence interval (CI). The highest Case fatality rate (40.78%; 95% CI = 29.74%-51.84%) was reported among the elderly age group. The Case fatality rate among the different age groups was statistically significant (P =.00001). The highest and lowest Case fatality rate were estimated to be (5.04%; 95% CI = 3.57%-6.51%) and (4.48%; 95% = 0.00%-9.43%) in the western and middle regions, respectively; however, there was no statistical difference (P =.4%) between the regions. The study found a high Case fatality rate of COVID-19 among Libyans, with flattened curve patterns but uneven distribution. Age-related factors significantly influenced the case fatality rate, with the elderly reporting higher rates.